The Monster Mac and Cheese Party - Parr, Todd (New York : Little, Brown and Company, 2023)
Monsters bring their favorite mac and cheeses to a wacky potluck. Includes recipes for vegan mac and Todd mac.
new kids book 2023 fall.
Ages 4-8.
Keywords: Dinners and dining; Cooking; Monsters -- Fiction; Parties -- Fiction; Picture books; Monster fiction; Picture books